Diversifikasi Usaha Dan Pengaruh Terhadap Pendapatan Petani Padi Sawah Pasca Kerusakan Bendungan Irigasi Krueng Pasee di Desa Keutapang Kecamatan Syamtalira Aron - Riani Riani; Suryadi Suryadi; Barmawi Barmawi; Salamah Salamah (Universitas Galuh, 2026)
The damage to the Krueng Pasee irrigation dam caused a decline in wet-rice production in North Aceh Regency, decreasing from 427,455 tons in 2019 to 388,190 tons in 2021. However, some farmers continued farming by adjusting to the rainy season. Meanwhile, other farmers chose not to engage in agricultural activities during the dry season, requiring strategies to sustain their livelihoods through business diversification as an additional source of income. This study aims to identify the types of business diversification and the factors influencing the income of wet-rice farmers after the irrigation dam damage. The research area was determined using purposive sampling. A total of 30 farmers were selected as samples using a simple random sampling technique. Data were analyzed using qualitative descriptive analysis to describe the business diversification carried out by wet-rice farmers, while the influence of farmer characteristics on income was analyzed using quantitative descriptive analysis with multiple linear regression. The results showed that wet-rice farmers in Keutapang Village engaged in two types of business diversification: non-rice farming and non-farm businesses. The average monthly income obtained from alternative non-farm sources was higher than that from non-rice farming activities because the village is located close to the sub-district capital, making it easier for farmers to work outside agriculture by offering services or trading. The variables of gender and experience in alternative jobs had a significant effect on alternative income, while age and education variables had no significant effect on income.